Behind the kitchen door - Jayaraman, Sarumathi, 1975- (ILR Press, 2013)
Uncovers the inequities of restaurant labor in the United States, from low wages and poor employee benefits to sexual harassment, unsafe working conditions, and the hypocrisy of ethical, free-trade restaurants.